145 The role of the bovine respiratory microbiota in health and disease. (7th December 2018) - Alexander, T
Abstract: Bovine respiratory disease (BRD) remains the most common cause of morbidity and mortality in feedlot cattle, resulting in significant economic losses. It is a multifactorial disease but bacterial species, including Histophilus somni, Mannheimia haemolytica, Mycoplasma bovis, and Pasteurella multocida are frequently implicated. The upper respiratory tract is a reservoir of these opportunistic pathogens, which can proliferate and infect the lungs when cattle immunity is compromised due to stress or primary viral infections. High risk cattle populations (e.g. recently weaned, lightweight, commingled, auction market-derived) entering feedlots are most susceptible to BRD, and as such, are frequently administered metaphylactic antibiotics to mitigate BRD. While research has mainly focused on pathogens, there are an increasing number of studies showing the importance of the host's microbiota in relation to health. It is becoming clear that the resident microbiota of the respiratory tract have a critical role in colonization and resistance against bacterial pathogens. Establishment and stability of the respiratory microbiota is critical to cattle health, and disruption can predispose to pathogenesis. Recent studies by our team and others have shown that the respiratory bacteria of cattle can be perturbed by industry management practices. These disturbances coincide with the time when feedlot cattle are most susceptible to BRD. For example, transportation to a feedlot, change in diet composition, and antibiotic administration influence the respiratory microbiota of cattle. In addition, the microbiota of the nasopharynx and trachea are different in cattle that are healthy, compared to those diagnosed with BRD. Combined, these data suggest that microbiota-based interventions could provide new opportunities for managing BRD in cattle, in place of antibiotics. In this presentation, an overview of current knowledge on the bovine respiratory microbiota will be given, as well future directions involving manipulation of the microbiota to improve cattle health.